The Effect of Cooking and Cooling Chickpea Pasta on Resistant Starch Content, Glycemic Response, and Glycemic Index in Healthy Adults - Adrianna Bojarczuk; Paulina Kęszycka; Krystian Marszałek; Danuta Gajewska (Metabolites)
Background/Objectives: Legume seeds, such as chickpeas, are a rich source of resistant starch (RS) and have a low glycemic index (GI). The aim of this study was to evaluate the effect of cooking and cooling chickpea pasta on the RS content, glycemic response, and GI in healthy subjects. Methods: Twelve healthy subjects of both sexes, aged 18–65 years, participated in this study. Each person consumed two standardized portions of chickpea pasta: (i) freshly cooked (FCP) and (ii) cooked chickpea pasta which was cooled for 24 h at 4 °C and reheated before consumption (CCP). Glucose solution was provided as a reference food. Participants consumed chickpea pasta in a random order. GI measurements were completed using the standard methodology and calculated according to the ISO 2010 standard. Results: The cooling and reheating process significantly increased the RS content of boiled chickpea pasta (from 1.83 g/100 g to 3.65 g/100 g) and had a beneficial effect on postprandial glycemia in healthy individuals. The CCP pasta had a significantly lower GI value than the FCP pasta (33 vs. 39, p = 0.0022). A significant difference in the glucose, as identified by the incremental area under the curve (IAUC), was observed between the CCP and FCP (1327.9 ± 414.8 mg/dL/min vs. 1556.1 ± 456.9 mg/dL/min, p = 0.0022). The cooling–reheating process did not affect the sensory attributes of the chickpea pasta. In general, the overall acceptability of the CCP pasta was similar to that of the FCP pasta. Conclusions: The results of our study support the hypothesis that a reduced glycemic response after simple changes in technological intervention leads to a decrease in postprandial blood glucose and GI. This can be helpful for people who need to control postprandial glycemia.